2011
DOI: 10.1128/mbio.00245-10
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Communities of the Upper Respiratory Tract and Otitis Media in Children

Abstract: Streptococcus pneumoniae asymptomatically colonizes the upper respiratory tract of children and is a frequent cause of otitis media. Patterns of microbial colonization likely influence S. pneumoniae colonization and otitis media susceptibility. This study compared microbial communities in children with and without otitis media. Nasal swabs and clinical and demographic data were collected in a cross-sectional study of Philadelphia, PA, children (6 to 78 months) (n = 108) during the 2008-2009 winter respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
216
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(237 citation statements)
references
References 54 publications
(52 reference statements)
12
216
8
1
Order By: Relevance
“…2,3 During the following years multiple epidemiological studies in different geographical regions observed similar findings of a negative association between carriage of S. pneumoniae and S. aureus in young children. [4][5][6][7][8] The carriage of both species was associated with age, with the peak S. pneumoniae carriage and lowest S. aureus carriage at 6 months to 3 years [4][5][6][7][8][9][10] and peak S. aureus colonization at age <6 months and 5-7 y 11 The negative association was significant even after adjusting for age, but this interference was not observed in older children and adults. 8,12 Interestingly, most studies 2,3,5,9 found that the inverse correlation between S. pneumoniae and S. aureus was significant only for carriage of vaccine-type S. pneumoniae strains, which were carried more commonly before the introduction of the pneumococcal vaccine.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…2,3 During the following years multiple epidemiological studies in different geographical regions observed similar findings of a negative association between carriage of S. pneumoniae and S. aureus in young children. [4][5][6][7][8] The carriage of both species was associated with age, with the peak S. pneumoniae carriage and lowest S. aureus carriage at 6 months to 3 years [4][5][6][7][8][9][10] and peak S. aureus colonization at age <6 months and 5-7 y 11 The negative association was significant even after adjusting for age, but this interference was not observed in older children and adults. 8,12 Interestingly, most studies 2,3,5,9 found that the inverse correlation between S. pneumoniae and S. aureus was significant only for carriage of vaccine-type S. pneumoniae strains, which were carried more commonly before the introduction of the pneumococcal vaccine.…”
Section: Introductionmentioning
confidence: 91%
“…45 In line with this, Laufer et al observed that S. pneumoniae colonization was more frequently detected when the microbiome had lower population diversity. 4 S. aureus has also been shown to affect and be affected by other species in the upper respiratory niche. Analysis of the nasal microbiome by Lina et al found a negative association between Corynebacterium species and S. aureus carriage, 28 and similarly, Yan et al found that various species of Corynebacterium were either positively (C. accolens) or negatively (C. pseudodiphtheriticum) associated with the presence of S. aureus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of Corynebacterium spp. in the nasal cavity is often inversely correlated with pathogenic Streptococcus pneumoniae (58). Like S. epidermidis, Corynebacterium accolens also utilizes a secreted enzyme, LipS1, to interfere with a competitor.…”
mentioning
confidence: 99%
“…The description of the infant respiratory microbiome is only just beginning (45,56,57), but a recent study found an association between early-life H. influenzae nasopharyngeal colonization and microbial population perturbations brought on by viral infection and antibiotic treatment (49). A long-term study performed in Denmark showed that children who exhibited signs of asthma and wheezing by age 7 years had an abnormal immune response to H. influenzae at age 6 months, as measured by cytokine levels and T-cell responses in stored peripheral blood mononuclear cells (PBMCs) obtained from the study participants.…”
Section: Discussionmentioning
confidence: 99%